Pengaruh Rasio Likuiditas, Profitabilitas, dan Solvabilitas terhadap Return Saham pada Perusahaan Industri yang Terdaftar di Indeks Saham Syariah Indonesia (ISSI) Tahun 2019-2023 - Rofiatun Munawaroh Rofiatun Munawaroh; Addiarahman Addiarahman (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2026)
Stock return is one of the main indicators considered by investors in making investment decisions, as it reflects the level of profit obtained. Stock return can be influenced by a company’s financial performance, which is reflected in liquidity, profitability, and solvency ratios. This study aims to analyze the effect of liquidity, profitability, and solvency ratios on stock return of industrial sector companies listed in the Indonesian Sharia Stock Index (ISSI) during the 2019–2023 period. The research employs a quantitative approach using secondary data obtained from the companies’ annual financial statements. The sampling technique used is purposive sampling, resulting in 14 companies selected as research samples over the observation period. Data analysis was conducted using descriptive statistics, panel data regression, classical assumption tests, and hypothesis testing with the assistance of E-Views 12 software. The results show that partially, the liquidity ratio has a negative and significant effect on stock return, the profitability ratio has a positive and significant effect on stock return, while the solvency ratio has no significant effect on stock return. Simultaneously, liquidity, profitability, and solvency ratios have a significant effect on stock return, with a coefficient of determination of 24%, while the remaining 76% is influenced by other variables outside the research model. These findings indicate that financial ratios have a limited contribution in predicting stock return; therefore, future research is recommended to incorporate more diverse independent variables.